Differences in Immunoglobulin Light Chain Species Found in Urinary Exosomes in Light Chain Amyloidosis (AL) - Ramirez-Alvarado, Marina (Public Library of Science, 2012)
Renal involvement is a frequent consequence of plasma cell dyscrasias. The most common entities are light chain amyloidosis, monoclonal immunoglobulin deposition disease and myeloma cast nephropathy. Despite a common origin, each condition has its own unique histologic and pathophysiologic characteristic which requires a renal biopsy to distinguish. Recent studies have shown urinary exosomes containing kidney-derived membrane and cytosolic proteins that can be used to probe the proteomics of the entire urinary system from the glomerulus to the bladder. In this study, we analyzed urine exosomes to determine the differences between exosomes from patients with light chain amyloidosis, multiple myeloma, monoclonal gammopathy of undetermined significance, and non-paraproteinemia related kidney disease controls. In patients with light chain amyloidosis, multiple myeloma and monoclonal gammopathy of undetermined significance, immunoreactive proteins corresponding to monomeric light chains were found in exosomes by western blot. In all of the amyloidosis samples with active disease, high molecular weight immunoreactive species corresponding to a decamer were found which were not found in exosomes from the other diseases or in amyloidosis exosomes from patients in remission. Few or no light chains monomeric bands were found in non-paraproteinemia related kidney disease controls. Our results showed that urinary exosomes may have tremendous potential in furthering our understanding of the pathophysiology and diagnosis of plasma cell dyscrasia related kidney diseases.